The impact of debriefing modalities on nurse practitioner students' knowledge and leadership skills in managing fatal dysrhythmias: A pilot study. (January 2020) - Alhaj Ali, Abeer; Miller, Elaine; Ballman, Kathleen; Bakas, Tamilyn; Geis, Gary; Ying, Jun
Abstract: Acute care nurse practitioners (ACNPs) require special training and educational preparation to meet their role expectations. Using high fidelity simulation with debriefing modalities is considered one of the innovative learning strategies in graduate nursing. No studies have investigated debriefing modalities in nurse practitioner programs specially ACNPs leadership skills. The purpose of this study was to examine the difference in students' knowledge, code team leader skills and self-efficacy using two debriefing modalities. A two group, pretest-posttest quasi-experimental design was used. Students were divided into video-assisted debriefing group vs. verbal debriefing following a simulation scenario of managing emergency codes. There were no significant differences between the two groups in knowledge acquisition/retention, leadership skills, and self-efficacy, but there was a significant difference in self-efficacy in both groups between two-time points. There was a general improvement in teams' performance. Students preferred verbal debriefing over video-assisted debriefing. The debriefing session plays an important role in graduate nursing education. Acute care nurse practitioners are lacking a formal leadership training to meet their advanced role. Nurse Educators, and simulation/debriefing leaders may benefit from our study results to develop a structured, formal curriculum and educational instruction focusing on acute care nurse practitioners' role change especially leading a resuscitation team. Highlights: Simulation and debriefing are important in teaching ACNP leadership skills and self-efficacy. Both video-assisted debriefing and verbal debriefing are effective in teaching advanced skills. It is important to examine the impact of debriefing modalities in ACNP students' leadership skills. ACNPs' advanced role require special leadership skills training and more structured curriculum. Further studies on debriefing experiences in graduate nursing education are needed.